Features of phototropic response of zooplankton to paired photostimulation under adverse environmental conditions - Dyomin, Victor V.; Morgalev, Yuri N.; Morgalev, Sergei Yu; Morgaleva, Tamara G.; Davydova, Alexandra Yu; Polovtsev, Igor G.; Kirillov, Nikolay; Olshukov, Alexey S.; Kondratova, Oksana (Environmental monitoring and assessment)
Our previous studies showed that the change in the plankton response to light could be an indicator of environmental pollution. This study experimentally reveals that the response of Daphnia magna Straus and Daphnia pulex plankton ensem- bles to photostimulation depends on the intensity of the attracting light. This makes it difficult to identify the occurrence and change of pollutant concentration. The large variability in the magnitude of the behav- ioral response is caused by the nonlinear response of plankton ensembles to the intensity of the attrac- tor stimulus. As the intensity of the photostimulation increases, the variability of the phototropic response passes through increase, decrease, and relative stabi- lization phases. The paper proposes a modification of the photostimulation method—paired photostimu- lation involving successive exposure to two pho- tostimuli of increasing intensity. The first stimulus stabilizes the behavioral response, while the increase in response to the second stimulus makes it possible to more accurately assess the responsiveness of the plankton ensemble. The paper studies the sensitivity of the method of paired stimulation of the behavio- ral response of different types of freshwater plankton ensembles: Daphnia magna Straus, Daphnia pulex to the effects of pollutants (potassium bichromate, microplastic). The study demonstrates good reliabil- ity and increased sensitivity of this method of detect- ing changes in environmental toxicity compared to single photostimulation or traditional bioindication through the survival rate of test organisms.